Simulación de escenarios mejorados de estimulación reactiva en pozos productores de un campo a en la cuenca de los Llanos Orientales mediante inteligencia artificial (2024)
The fundamental objective of the study presented in this document was to improve the reactive matrix stimulations implemented in three producing wells of the Guadalupe formation located in Field A of the Eastern Llanos Basin by simulating improved scenarios through artificial intelligence. For the development of the study in the (3) three wells and in order to increase crude oil production and reduce formation damage, simulation software called Computering Modeling Group (CMG) and the sub-systems were used. tools that helped in the creation of the well models, the modeling of the produced fluids and the formation damage model. Continuing with the stimulation optimization procedure, the SLB company software called Pipesim was used to establish the IPR and VLP curves that allowed evaluating the selection of improvement scenarios as well as the description of the productive performance of wells with damage from training, in turn the nodal analysis made it easier to establish the current operating conditions.